The Commonwealth Caribbean and the challenges of institutional exclusion - Clegg, Peter (2008)
Evaluates the changes that have taken place in the political economy of global trade, particularly the growing influence of international organizations and their rules and norms, and the institutional exclusion of the Commonwealth Caribbean that has resulted.